CD4 Recovery on Antiretroviral Therapy Is Associated With Decreased Progression to Liver Disease Among Hepatitis C Virus-Infected Injecting Drug Users. (28th February 2015) - Anderson, Jeffrey P.; Horsburgh, C. Robert; Williams, Paige L.; Tchetgen Tchetgen, Eric J.; Nunes, David; Cotton, Deborah; Seage, George R.
Abstract: Background.  Human immunodeficiency virus (HIV) coinfection accelerates liver disease progression in individuals with chronic hepatitis C. We evaluated the associations of CD4, HIV RNA, and antiretroviral therapy (ART)-induced CD4 recovery with liver diagnoses in a prospective cohort of injecting drug users (IDUs). Methods.  We evaluated 383 coinfected IDUs in the Boston area, prospectively observed for a median of 1.8 years. Liver disease progression included the first occurrence of hepatocellular carcinoma, variceal bleeding, ascites, encephalopathy, or death due to hepatic failure. Multivariable-adjusted extended Cox models were specified to estimate hazard ratios (HRs) for comparisons of CD4, change in CD4 (from nadir), and HIV RNA with respect to liver disease progression events. Results.  Twenty-four persons experienced a liver disease progression event over 1155 person-years (2.1 per 100 person-years), including 20 deaths attributed to end-stage liver disease (1.7 per 100 person-years). CD4 at baseline and over follow-up strongly predicted liver disease progression (baseline CD4 <200 vs ≥200: HR = 5.23, 95% confidence interval [CI], 2.30–11.92; time-updated CD4 <200 vs ≥200: HR = 11.79, 95% CI, 4.47–31.07). Nadir CD4 was also a strong indicator (<100 vs ≥100: HR = 3.52, 95% CI, 1.54–8.06). A lack of CD4 recovery (failure to increase 100 cells over nadir) among ART initiators was associated with increased risk (HR = 7.69; 95% CI, 2.60–22.69). Human immunodeficiency virus RNA was not significantly associated with liver disease progression. Conclusions.  Impaired immune function was highly predictive of liver disease progression in this cohort of IDUs, and a lack of CD4 recovery on ART was associated with increased risk of progression to HCV-associated liver disease.